Pengaruh Dukungan Organisasi, Kepuasan Kerja dan Keterlibatan Pegawai Terhadap Kinerja Pegawai Kantor Kecamatan Batam Kota - Anggraini, Maya Karnia; Herman, Hendri; Sumardin, Sumardin (eScience Humanity Journal, 2025)
This study aims to examine the effect of organizational support, job satisfaction, and employee engagement on employee performance at the Batam Kota District Office. In the context of increasing public service demands and administrative responsibilities, employee performance has become a critical factor in ensuring effective and efficient governance at the local government level. However, variations in employee performance indicate the presence of organizational and psychological factors that require empirical investigation. This research employs a quantitative approach using a survey method. The population of this study consists of all employees working at the Batam Kota District Office, totaling 85 individuals, and the entire population was used as the research sample through a census technique. Data were collected using structured questionnaires and analyzed using multiple linear regression analysis to determine both partial and simultaneous effects of the independent variables on employee performance. The findings reveal that organizational support, job satisfaction, and employee engagement simultaneously have a positive and significant effect on employee performance. Partially, each independent variable also shows a significant influence on performance, indicating that employees who perceive higher organizational support, experience greater job satisfaction, and demonstrate stronger engagement tend to exhibit better work performance. The coefficient of determination indicates that these three variables contribute 3.2% to employee performance, while the remaining 96.8% is influenced by other factors not examined in this study. The results highlight the importance of strengthening organizational support systems, improving job satisfaction through fair compensation and career development opportunities, and encouraging employee involvement in decision-making processes. These efforts are expected to enhance employee performance and support the achievement of high-quality public services. This study contributes to human resource management literature, particularly in the public sector, and provides practical insights for policymakers in improving employee performance within government institutions.